Islamic Studies in Madrasah Aliyah Al-Maarif Singosari Malang During the Covid-19 Pandemic - Moh Eko Nasrulloh (Universitas Yudharta Pasuruan, 2020)
Juvenile delinquency in the form of violence is still common in the community even during the covid-19 pandemic. violence has several contributing factors. Education as a form of institution that seeks to prevent violence from inside and outside students through Islamic religious learning. This study discusses Islamic religious learning efforts carried out at MA Almaarif Singosari Malang during the covid-19 pandemic. Kulaitatif research is used as a method in discussing the title so that conclusions are obtained as answers.interviews and observations are used in collecting data. The research results are islamic learning and at MA Almaarif Singosari Malang is conducted online and offline. Learning objectives are conveyed in learning in both ways. Media, learning resources, and teaching materials are available in both ways of learning. Conducive, proactive, flexible learning atmosphere is manifested in online and face-to-face learning.